Comparação entre índices dinâmicos e volumétricos de pré-carga em cães submetidos à hemorragia moderada seguida de reposição volêmica - Celeita-Rodríguez, Nathalia [UNESP] (2016)
Objective: To evaluate the effects moderate blood loss followed by volume replacement (VR) on intra-thoracic blood volume index (ITBVI), global end-diastolic volume index (GEDVI), pulse pressure variation (PPV), and stroke volume variation (SVV). Study design: Prospective, randomized study. Animals: Seven English Pointer dogs (20.0–31.2 kg). Methods: Anesthesia was maintained with sevoflurane under volume-controlled ventilation and atracurium induced neuromuscular blockade. End-expired sevoflurane (ETsevo) concentrations were adjusted to inhibit heart rate and mean arterial blood pressure (MAP) changes in response to nociceptive stimulation (< 20% relative change). Data recorded at baseline, after withdrawal of 14–16 mL kg-1 of blood volume and after VR with autologous blood. Results: Anesthesia was maintained with 3.1 ± 0.3 vol% of ETsevo concentrations. One outlier was excluded from the statistical analysis. Hemorrhage significantly (P < 0.05) decreased cardiac index (CI), stroke index (SI), and MAP by 20–25% from baseline (percent changes in mean values). Volume replacement significantly increased MAP in comparison to values recorded after hemorrhage (31% increase); while CI and SI were significantly increased after VR in comparison hemorrhage and to baseline (29–30% above baseline). The ITBVI and GEDVI were decreased by 15% from baseline after blood loss; while VR significantly increased ITBVI and GEDVI by 21% from values recorded after hemorrhage. Relative decreases in ITBVI induced by hemorrhage represented 10–44% of the blood volume withdrawn among individual animals. No significant changes in PPV and SVV were observed throughout the observational period. Conclusions and clinical relevance: Volumetric indexes of preload, but not PPV and SVV, reflect changes in volume status induced by moderate blood loss and VR. However, a high inter-individual variability of changes in ITBVI and GEDVI induced by similar degrees o hemorrhage suggest that these indexes are inaccurate estimate the severity of acute hemorrhage.